FREKUENSI SOIL TRANSMITTED HELMINTHS PADA MURID SD MUHAMMADIYAH SURAU GADANG KECAMATAN NANGGALO PADANG - Sakaleak, Damerita; Risdawati, Renny; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACTSTH worm infection is more commonly infects children, especially school age, because at the age of school children are actively playing in soil contaminated by feces and lack of attention to personal hygiene.The experiment was conducted in June 2013. The method used in this study is a descriptive survey method. The population in this study were all students of SD Muhammadiyah Surau Gadang 76 people students. Sampling was done by total sampling by many students who collected the sample of 72 students. Examination of a stool sample done at the Laboratory of Biology Education Program STKIP PGRI Â Sumatera Barat using the direct method.The study of elementary students Muhammadiyah Surau Gadang District Nanggalo Padang showed that 62.5% were infected with STH 45 students and are not infected with STH 37.5%. Frequency of STH infections in Muhammadiyah Surau Gadang elementary school students found 37.5% of species Ascaris lumbricoides, Trichuris trichiura 19.4%, Hookworm (Necator americanus and Ancylostoma duodenale) 5.4%. The highest frequency of STH species found in SD Muhammadiyah students Surau Gadang is Ascaris lumbricoides.Â